KINERJA TENAGA PENJUALAN PT.NASMOO JAWA TENGAH DAN DIY - Amri, Syaeful (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2015)
The purpose of this research was to test the influences of of learning orientation, quality of training, sales force competence, smart working orientation toward sales force performance to achieve sales targets. 7/â€ºe osage o/ these variables was able to solve the arising problem within PT. Nasmoco Central Java and DIY.The Research aims to analyze the influences of factors toward performance of sales force, based on the case, a theoretical model and 4 hypotheses are accomplished to be tested using Structural Equation Model (SEM). The sample of this research is 100 sales pemon irâ€º PT. Nasmoco Jawa Tengah and DIY.From the result of this analysis, Structural Equation Model has fulfilled criteria of Goodness Fit Index; W (chi square) 100,219, probability 0. 109 (eâ€0.05), RMSEA 0.044 (dâ€0.08), GFI 0.887 (eâ€0.90), A GFI 0.838 (eâ€0.90), TLI 0.985 (eâ€0.95), CFI 0.988 (eâ€0.95).The result of the analysis showed that learning orientation, quality of training, and sales force competence strongness an positive influence, which is significant to sales force performance and sales targets. The empirical result indicated that to increase sales targets of PT. Nasmoco Central Java and DIY, management need to pay attention on factors learning orientation, quality of training, sales fnrce competence, and sales force performance, because that is he factors that effect high or low level of achieving sales targets.